Energy Metabolism in Residents in the Low- and Moderate Altitude Regions of Central Asia with MAFLD and Type 2 Diabetes Mellitus - Toktogulova, Nurgul; Breidert, Matthias; Eschbach, Judith; Kudaibergenova, Indira; Omurzakova, Uulkan; Uvaidillaeva, Feruzakhan; Tagaeva, Bermet; Sultanalieva, Roza; Eftekhari, Pierre (Hormone and Metabolic Research, 2024)
The knowledge about the features of energy metabolism in MAFLD in the population living at different climatic and geographic heights is lacking. The goal of this study is to explore the biochemical parameters of blood and erythrocyte energy consumption in patients with MAFLD with and without DM2 living in the low- and moderate-altitude regions of Central Asia. Our study was carried out on patients living in low-altitude mountains: Bishkek, altitude=750–800 m; n=67 (MAFLD with DM 2: n=24; MAFLD without DM2: n=25; control: n=18), and At-Bashy District, Naryn Region, altitude=2046–2300 m; n=58 (MAFLD with DM2: n=28; MAFLD without DM2: n=18; control: n=12). Non-alcoholic fatty liver disease was diagnosed according to history, laboratory tests, liver ultrasound, and exclusion of other liver diseases. The level of liver fibrosis was determined using the FIB-4 score. Blood adenosine 5′-triphosphate (ATP) was determined using the CellTiter-Glo method. Healthy residents living in moderate altitudes have significantly higher levels of cytosolic ATP in their blood (p+≤+0.05) than residents living in low mountains. MAFLD is characterized by an increase in the level of ATP concentration in their blood. ATP concentration decreased significantly in patients with MAFLD with DM2 living in moderate-altitude in comparison to those living in low-altitude mountains. The results suggest that chronic altitude hypoxia leads to a breakdown in adaptive mechanisms of energy metabolism of ATP in patients with MAFLD with type 2 DM.
Keywords: fatty liver disease; ATP; diabetes mellitus